2009
DOI: 10.1007/s10409-008-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of vortex-induced vibrations of a cylinder near a rigid plane boundary in steady flow

Abstract: In this study, the vortex-induced vibrations of a cylinder near a rigid plane boundary in a steady flow are studied experimentally. The phenomenon of vortex-induced vibrations of the cylinder near the rigid plane boundary is reproduced in the flume. The vortex shedding frequency and mode are also measured by the methods of hot film velocimeter and hydrogen bubbles. A parametric study is carried out to investigate the influences of reduced velocity, gap-to-diameter ratio, stability parameter and mass ratio on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…The velocities that induce cylinder vibration span from u 0 ¼15.89 to 19.09 cm/s (V r ¼5.64-6.78), which is a rather narrow range. This phenomenon agrees with the observations in the high-m * ζ condition by Yang et al (2009), who found that significant vibrations appear within a narrow range with V r E5.09-6.51 in the intermediate region. Fig.…”
Section: Vibrating Characteristics Of a Circular Cylinder With Differsupporting
confidence: 92%
See 2 more Smart Citations
“…The velocities that induce cylinder vibration span from u 0 ¼15.89 to 19.09 cm/s (V r ¼5.64-6.78), which is a rather narrow range. This phenomenon agrees with the observations in the high-m * ζ condition by Yang et al (2009), who found that significant vibrations appear within a narrow range with V r E5.09-6.51 in the intermediate region. Fig.…”
Section: Vibrating Characteristics Of a Circular Cylinder With Differsupporting
confidence: 92%
“…Fredsøe et al (1987) observed that the vibrating characteristics of the cylinder is clearly influenced by the boundary when G 0 /Do1.0. Yang et al (2009) investigated the amplitude and frequency responses of a vibrating cylinder under different G 0 /D, and found an obvious difference between larger G 0 /D (G 0 /D 40.66) and smaller ones (G 0 /Do0.3). Wang et al (2013) used PIV to investigate the effect of a plane boundary on vortex formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al (2011) compared the dynamic response of cylinder near a deformable wall in both 1-DoF and 2-DoF cases. Yang et al (2009) showed that the dimensionless vibration frequency for smaller e/D of 0.06 and 0.30 are much larger than those for larger e/D of 0.66 and 0.88, respectively, at the same reduced velocity. For smaller mass ratio m n , the vibration range is larger.…”
Section: Introductionmentioning
confidence: 92%
“…VIV of a pipeline, which has been considered as one of the most important reasons for a pipeline failure, may occur when the ocean flow crossing the pipeline is larger than a certain value. Most existing studies on VIV were mainly focused on the vibration amplitude and frequency for a wall-free (Feng, 1968;Sarpkaya, 2004;Govardhan & Williamson, 2006;Vandiver, 2012) or near-bed cylinder (Jacobsen et al, 1984;Yang et al, 2009;Zang & Gao, 2014). However, the critical condition for the onset of VIV is also a crucial parameter in practical engineering, as it is closely related to the allowable length for avoiding VIV of the spanning pipeline.…”
Section: Introductionmentioning
confidence: 99%